Norway spruce somatic embryogenesis benefits from proliferation of embryogenic tissues on filter discs and cold storage of cotyledonary embryos - Välimäki, Sakari; Teyssier, Caroline; Tikkinen, Mikko; Delile, Armelle; Boizot, Nathalie; Varis, Saila; Lelu-Walter, Marie-Anne; Aronen, Tuija (Frontiers in Plant Science, 2022)
Vegetative propagation opens opportunities for the multiplication of elite tree progeny for forest regeneration material. For conifers such as Norway spruce (Picea abies) the most efficient vegetative propagation method is seed multiplication through somatic embryogenesis. Efficient culture methods are needed for somatic embryogenesis to be commercially viable. Compared to culturing as clumps, filter disc cultures can improve the proliferation of embryogenic tissue (ET) due to more even spread and better developmental synchronization. In this study, ET proliferation on filter discs was compared to proliferation as clumps. The study comprised 28 genotypes in four trials. The benefits of adding a pre-maturation step and the selection of fresh ET for the subculture were evaluated. Pre-maturation on hormone-free media before maturation did not significantly improve embryo yield but improved greenhouse survival from 69% to 80%, although there was high variation between lines. Filter disc cultivation of ET did result in better growth than in clumps but was more dependent on ET selection and the amount of ET than the clump cultivation method. Filter proliferation also favors certain lines. Post-maturation storage can be used to change the storage compound composition of the produced mature embryos. The embryo storage compound profile was analyzed after post-maturation cold storage treatments of 0, 4, 8, 31, and 61 weeks and compared to that of the zygotic embryos. Cold storage made the storage compound profile of somatic embryos closer to that of zygotic embryos, especially regarding the raffinose family oligosaccharides and storage proteins. Sucrose, hexose, and starch content remained higher in somatic embryos even through cold storage. Prolonged storage appeared less beneficial for embryos, some of which then seemed to spontaneously enter the germination process.